Olfactory processing and Alzheimer’s disease - Rosalinda Guevara-Guzmán (2006)
Most of the studies on olfactory perception in Alzheimer´s Disease show a reduction or loss of ability to identify recognize and detect scents. This loss is noticeable during the first stages of Alzheimer´s Disease. Sensitivity loss in terms of detection thresholds can occur but as the cognitive impairment increases there are also problems with odor identification or memory. In our studies we have demonstrated that the familiarity of odors plays an important role in identifying scents. Other elements that may affect odor evaluation are its dispersal vehicle and concentration.